Pendaftaran Semester Pendek Program Studi Pendidikan Jasmani FKIP Universitas Dehasen Bengkulu Berbasis Online - Dimas Mekar Ayu Fatimah; Asnawati Asnawati; Achmad Fikri Sallaby (Jurnal Media Infotama, 2025)
Advances in information technology have made a significant contribution to improve the efficiency of educational systems, including in academic administrative processes such as short-semester registration. At the Physical Education Study Program, Faculty of Teacher Training and Education, Universitas Dehasen Bengkulu, the short-semester registration process is still conducted manually, which often leads to challenges such as slow processing, high error rates, and difficulties in data management. To overcome these problems, a web-based short semester registration information system was developed using PHP programming language and MySQL database. This system allows students to register online and provides multi-level login features for administrators and students, course quota monitoring, and automatic data storage. The research method used was descriptive with data collection techniques through observation, interviews, and literature study. The result of this research is web application called Sisfo-SP.site, which provides a practical and efficient solution for the short semester registration process in campus